2017
DOI: 10.3233/jad-170364
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease: The Alternative Serotonergic Hypothesis of Cognitive Decline

Abstract: The pathognomonic feature of Alzheimer's disease is a loss of declarative memory. This has generally been attributed to early involvement of medial temporal lobe structures with neurofibrillary tangles and loss of neurons in the entorhinal cortex. However, there has been a re-emerging emphasis on the causal role of brainstem monoaminergic nuclei as involvement of the cholinergic basal forebrain loses prominence. The rejection of this latter theory of cognitive decline is related to inconsistencies in time cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 57 publications
0
16
0
1
Order By: Relevance
“…No experimental study, however, has yet provided evidence of a significant structural or functional change in this nucleus at the preclinical stage of AD. At present, this link has only been hypothesised 9 .…”
Section: Introductionmentioning
confidence: 94%
“…No experimental study, however, has yet provided evidence of a significant structural or functional change in this nucleus at the preclinical stage of AD. At present, this link has only been hypothesised 9 .…”
Section: Introductionmentioning
confidence: 94%
“…Alzheimer’s disease (AD) is one of the most common neurodegenerative diseases of the CNS, characterized by memory loss and cognitive dysfunction, and has a variety of neurological and psychiatric symptoms and behavioral disorders [45]. Pathologically, AD is marked by the presence of extracellular amyloid plaques (APs) and intracellular neurofibrillary tangles (NFTs) in the brain.…”
Section: Astrocytes Morphology and Functions In The Cnsmentioning
confidence: 99%
“…Inhibition of the dorsal raphe nucleus, the main serotonin source, alters impulsivity by reducing tolerance to delayed rewards and enhancing avoidance of difficulty selection 30,31 . As AD progresses, loss of serotonergic neurons and/or hyperphosphorylation of tau proteins accompany local neuroinflammation in the dorsal raphe 8,9,32,33 . Besides, as a result of re-analysis including a confound regressor (the number of motor response in each trial), hyperactivation of the dorsal raphe nucleus in AD model mice was observed as well.…”
Section: Discussionmentioning
confidence: 99%